2012
DOI: 10.1186/1476-7120-10-31
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative approach using multiple single parameters versus visual assessment in dobutamine stress echocardiography

Abstract: BackgroundA number of myocardial Doppler-derived velocity, strain myocardial imaging parameters (DMI) and speckle tracking imaging (STI) have been proposed for the quantification of myocardial ischemia during stress echocardiography. The purpose of the study was to identify the best single ultrasound quantitative parameter for prediction of significant coronary stenosis and compare it with visual assessment during dobutamine stress echocardiography (DSE).MethodsProspective analysis included data of 151 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Global and regional systolic myocardial deformation abnormalities at rest and during dobutamine stress in patients with CAD have been demonstrated in previous studies . Our study results indicate that GLS had a better predictive value than other diastolic and systolic strains and SR parameters or visual assessment.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Global and regional systolic myocardial deformation abnormalities at rest and during dobutamine stress in patients with CAD have been demonstrated in previous studies . Our study results indicate that GLS had a better predictive value than other diastolic and systolic strains and SR parameters or visual assessment.…”
Section: Discussionsupporting
confidence: 79%
“…Global and regional systolic myocardial deformation abnormalities at rest and during dobutamine stress in patients with CAD have been demonstrated in previous studies. [15][16][17][18][19][20][21][22][23][24][25][26] Our study results indicate that GLS had a better predictive value than other diastolic and systolic strains and SR parameters or visual assessment. GLS at high dobutamine doses has an AUC close to 1 and seems to be a very potent predictor of hemodynamically significant CAD.…”
Section: Discussionmentioning
confidence: 89%
“…In recent years, new non-Doppler speckle tracking techniques were validated for quantifying regional function. 17,19,27 The reason for this difference maybe that in our study, the patients were treated with late PCI, while in prior studies, patients were treated with pPCI, and our follow-up duration was longer, i.e., 6-9 months. 10,11,17,26 LV systolic characteristics post-MI can be evaluated by STE, including the myocardium peak systolic magnitude or velocity of different directions (peak systolic strain or strain rate of longitudinal, circumferential, and radial directions), LV mechanical dyssynchrony (SD of time to peak systolic strain), and postsystolic motion (postsystolic strain); however, which parameter can more powerfully predict LVr or clinical prognosis is unknown, particularly in AMI patients treated with late PCI.…”
Section: Discussionmentioning
confidence: 72%
“…Earlier studies by Balcells et al 23 and Swinburn et al 24 showed a correlation between regional wall-motion abnormalities and the results of perfusion contrast echocardiography assessing the viability of infarcted segments. 10,11,17,26 LV systolic characteristics post-MI can be evaluated by STE, including the myocardium peak systolic magnitude or velocity of different directions (peak systolic strain or strain rate of longitudinal, circumferential, and radial directions), LV mechanical dyssynchrony (SD of time to peak systolic strain), and postsystolic motion (postsystolic strain); however, which parameter can more powerfully predict LVr or clinical prognosis is unknown, particularly in AMI patients treated with late PCI. These techniques are angle independent and can differentiate between active contraction and passive displacement; thus, they are more accurate than Doppler tissue imaging for evaluating the regional function of the LV, 25 and several studies have reported that STE can be used to predict LVr or clinical prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…A number of myocardial Doppler derived velocity, strain myocardial imaging parameters and speckle tracking imaging and wall motion score index have been proposed for the quantification of myocardial ischemia during stress echocardiography (12-15). But in the routine echocardiographic examination, they all have difficulties in the early detection of the presence of myocardial ischemia to some extent, especially when angina or myocardial infarction has not yet occurred.…”
Section: Discussionmentioning
confidence: 99%